2012
DOI: 10.1136/amiajnl-2011-000609
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a new generation of computerized drug alerts in reducing the risk of injury from drug side effects: a cluster randomized trial

Abstract: ContextComputerized drug alerts for psychotropic drugs are expected to reduce fall-related injuries in older adults. However, physicians over-ride most alerts because they believe the benefit of the drugs exceeds the risk.ObjectiveTo determine whether computerized prescribing decision support with patient-specific risk estimates would increase physician response to psychotropic drug alerts and reduce injury risk in older people.DesignCluster randomized controlled trial of 81 family physicians and 5628 of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 45 publications
0
82
0
1
Order By: Relevance
“…Research shows that providing clinicians with alerts containing patient-specific risk factors can reduce the risk of injury. 47 Known modifying factors (such as patients’ genetic information, ethnicity, concomitant diseases, etc.) should be included in DDI alerts, and when factors are not known, the lack of information should also be stated.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that providing clinicians with alerts containing patient-specific risk factors can reduce the risk of injury. 47 Known modifying factors (such as patients’ genetic information, ethnicity, concomitant diseases, etc.) should be included in DDI alerts, and when factors are not known, the lack of information should also be stated.…”
Section: Resultsmentioning
confidence: 99%
“…The intervention reduced the risk of injury by 1.7 injuries per 1,000 patients (95% CI 0.2/1,000–3.2/1,000, P =0.02). The effect of the intervention was greater for patients with higher baseline risks of injury ( P <0.03) 72. A study by Tzeng et al determined the correlations between hospital-acquired injurious fall rates in US acute care hospitals and these institutions’ implementation levels of computerized systems.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the intervention was greater for patients with higher baseline risks of injury (P,0.03). 72 A study by Tzeng et al determined the correlations between hospital-acquired injurious fall rates in US acute care hospitals and these institutions' implementation levels of computerized systems. The results showed that computerized decision-support systems for DDI alerts, drug allergy alerts, and drug-laboratory interaction alerts were effective to inform practice for better interventions to reduce fall risk.…”
mentioning
confidence: 99%